Options for a Carbon Tax in Bangladesh - World Bank (Washington, DC: World Bank, 2018)
Carbon taxes can be win-win for Bangladesh. They can help show the world that Bangladesh is serious about climate mitigation, boosting the country’s influence in international negotiations and helping it to access financing and technology promised during the COP-21. They can play a role in nudging Bangladesh’s growth to a lower carbon and cleaner path, helping to make it more sustainable and improving environmental (and health) conditions for its citizens. They can help to raise additional resources – up to 1 percent of GDP – for social and economic development, including infrastructure investment. Some of the additional resources can be used to reduce taxes on labor or firms. Carbon taxes are much simpler to implement than most other taxes and most fuel costs would increase by only a few Taka per liter. At the same time, implementation needs to be done well to reduce opposition and win over firms and citizens. But Bangladesh can learn how other countries have succeeded. This Policy Note and accompanying Brief summarizes why carbon taxes make sense for Bangladesh and how to succeed.